The Problem of Hybridity - Speculative Space (Performance Philosophy)
Speculative Design offers a methodological toolbox with which to explore, and potentially legitimize, alternative models and modes of knowledge through world-building not based on, or not yet based on, socially normalised ‘truths’. However, a problematic dichotomy remains: whilst a neutral, transparent and universal truth may be a fantasy construct, the disturbance of such a construct through individual embodiments is no simple alternative. It requires a careful observation of the modes and assumptions, the premises and processes of different knowledge-generating practices within the confines of academia and beyond. In short, it requires actual (not simply professed) inter- and trans-disciplinarity; in other words: actual working together. So: How do we work together?